Immersion of Alginate Impression (Hydrocolloid Irreversible) On Two Percent Glutaraldehyde Prevent Contamination of Mycobacterium Tuberculosis on The Stone Cast - Rusmiany, P (BALI MEDICAL JOURNAL, 2013)
Objectives : to observe the effect of alginate impression (hydrocolloid irreversible) immersed on 2% glutaraldehyde on preventing contamination of Mycobacterium tuberculosis contamination on stone cast. Methods : This is an experimental research with post test only control group design, with alginate impression material (hydrocolloid irreversible) is immersed in the 2% glutaraldehyde  for 10, 15, and 25 minutes. Results :  This result shows that there is no Mycobacterium tuberculosis contamination on the stone cast after the immersion of alginate impression material for 10, 15, and 25 minutes. Immersion of alginate impression material (hydrocolloid reversible) in the glutaraldehyde 2% for 10 minutes is effective to prevent Mycobacterium tuberculosis contamination on the stone cast. Conclusions : Immersion of alginate impression on 2% glutaraldehyde for 10 minute was effective to prevent contamination of Mycobacterium tuberculosis
Keywords: Tuberculosis, Mycobacterium tuberculosis, alginate impression material, glutaraldehyde